How Co-Teaching May Contribute to Inclusion in Mathematics Education: A Systematic Literature Review - Malin Gardesten (MDPI AG, 2023)
This systematic literature review focuses on co-teaching and inclusion in mathematics education. Co-teaching, in which two or more teachers share responsibility for students' mathematical learning, can cater to students in need of special education. Through a narrative synthesis of 15 articles found through searches in 5 databases, this study investigates what characterizes co-teaching and how it contributes to students' inclusion in mathematics education. The review was conducted by identifying the focus, specifying review questions, determining studies to include, deciding on data to extract, and reporting the results. The findings show that co-teaching can contribute to spatial inclusion in mathematics education, implying that all students can be taught in the same classroom. Furthermore, co-teaching that contributes to social and didactical inclusion addresses all students' mathematical learning if it is flexibly organized. Therefore, students struggling to gain access to mathematics and those requiring extra challenges in mathematics learning can benefit from this teaching model.